2019
DOI: 10.1037/edu0000308
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ perceptions of students’ executive functions: Disparities by gender, ethnicity, and ELL status.

Abstract: Teacher-report is commonly used to assess executive functions (EFs) in schools, but teachers' perceptions of EF skills may be biased by students' demographic characteristics. In this short-term longitudinal study, we assessed whether students' gender, ethnicity, and English language learner (ELL) status predicted teachers' reports of students' EFs, beyond what would be expected based on direct assessment of EFs. In addition, we tested whether these associations changed between the fall and spring. Data were dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 77 publications
0
41
2
Order By: Relevance
“…As a related issue, our analysis of student cue utilization is based on student teachers' self-reports. This might have resulted in a social desirability bias of their answers and would be one explanation why our findings contradict previous ones in which teachers relied on unimportant student cues such as gender or SES (Meissel et al, 2017;Praetorius et al, 2017;Garcia et al, 2019;Brandmiller et al, 2020). In this context, our results might not fully reflect potentially problematic cue usage of student teachers.…”
Section: Limitationcontrasting
confidence: 91%
See 2 more Smart Citations
“…As a related issue, our analysis of student cue utilization is based on student teachers' self-reports. This might have resulted in a social desirability bias of their answers and would be one explanation why our findings contradict previous ones in which teachers relied on unimportant student cues such as gender or SES (Meissel et al, 2017;Praetorius et al, 2017;Garcia et al, 2019;Brandmiller et al, 2020). In this context, our results might not fully reflect potentially problematic cue usage of student teachers.…”
Section: Limitationcontrasting
confidence: 91%
“…Student teachers took into account in particular whether students showed general participation in learning activities, whether they raised their hands to contribute to classroom dialogue, and also considered the quality of students' verbal contributions frequently. That student teachers dominantly rely on such diagnostic student cues, contradicts previous research which showed that teachers also take into account misleading or unimportant information like student gender, ethnicity, immigration status, and SES in their assessment of student characteristics (Meissel et al, 2017;Praetorius et al, 2017;Garcia et al, 2019;Brandmiller et al, 2020). However, these studies used text vignettes to provide teachers with specific information about target students.…”
Section: High Judgment Accuracy Relates To a Utilization Of Particulamentioning
confidence: 87%
See 1 more Smart Citation
“…Direct assessments are considered to be more objective than teachers' reports, but they are less ecologically valid (Toplak, West, & Stanovich, 2013). In contrast, teachers' reports can be biased by students' demographic characteristics such as gender and race/ethnicity (Garcia, Sulik, & Obradović, 2019), but they have the advantage of capturing students' EF behaviors as they occur in naturalistic learning contexts. The inclusion of both types of assessments provides a more comprehensive and robust way to capture students' EF skills.…”
Section: Executive Functionsmentioning
confidence: 99%
“…Parental years of education was included as a covariate because of socioeconomic disparities in both EFs and achievement (Lawson, Hook, Hackman, & Farah, 2014;Reardon, 2011). Child gender and child race/ ethnicity were included as covariates due to previous research demonstrating gender and racial/ethnic differences on teacher-reported EFs (Garcia et al, 2019). Finally, child age was included as a covariate because it is associated with better EFs (Lee, Bull, & Ho, 2013) and less CP (Lepper et al, 2005).…”
Section: Covariatesmentioning
confidence: 99%